Contribution of MSME Sector towards Indian Economy with Special Reference to Kerala - Ms.Reshmi.V C, Dr.Rincy V Mathew (International Journal of Advanced Science and Technology, 2020)
The economic well being is the backbone of all nations. Numerous factors contributing to economy as employment, growth rate, exports, foreign earnings etc. Presently, MSME is considered as a catalyst for socio-economic development of nations. In India, MSME plays an outstanding contribution to overall economy and provides new opportunities at the grass root level. Furthermore, as every state in India, Kerala come up with its valuable inputs for the MSME sector. Therefore, it is important to know the performance of MSME sector in national level as well as state levels, so that can identify and implement new strategies for success. This study seeks to examine the performance and contribution of MSME in economy and to understand the status of MSME sector especially in Kerala.